Revitalisasi Permainan Tradisional untuk Mengurangi Ketergantungan Gadget dan Meningkatkan Aktivitas Fisik Siswa di SDN Kotakulon 03 - Muhammad Imanda Ilham; Ismaliain, Andara Erlyn; Gagas, Temi; Al-Ghozali, Ahmad Nur badar Sya’ban; Mutaqoful, Gading Dwi; Furqony, Ajriya Dhifan (Jurnal Pengabdian Nasional (JPN) Indonesia, 2025)
Traditional games offer various benefits for children's development and play a role in shaping their character. The purpose of this article is to (1) examine and promote the values embedded in the traditional game Benteng-Bentengan and (2) examine and promote the values embedded in the traditional game Gobag Sodor. From the issues addressed, it can be concluded that both Benteng-Bentengan and Gobag Sodor contain character-building values. The values found in the traditional game Benteng-Bentengan include honesty, sportsmanship, cooperation, responsibility, and unity. Meanwhile, the values found in the traditional game Gobag Sodor include honesty, sportsmanship, cooperation, strategic planning, and leadership. Based on the results of pre-tests, post-tests, and questionnaires given to parents, it was recorded that 90% of students at SDN Kotakulon 03 showed a decrease in their screen time on electronic devices. In addition, all students at SDN Kotakulon 03 have become familiar with and started playing traditional games, especially Gobag Sodor and Benteng-Bentengan.